2017
DOI: 10.1021/acschembio.7b00305
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Against Specific MUC16 Glycosylation Sites Inhibit Ovarian Cancer Growth

Abstract: Expression of the retained C-terminal extracellular portion of the ovarian cancer glycoprotein MUC16 induces transformation and tumor growth. However, the mechanisms of MUC16 oncogenesis related to glycosylation are not clearly defined. We establish that MUC16 oncogenic effects are mediated through MGAT5-dependent N-glycosylation of two specific asparagine sites within its 58 amino acid ectodomain. Oncogenic signaling from the C-terminal portion of MUC16 requires the presence of Galectin-3 and growth factor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…S6 ), an activity known from tumor cell growth regulation ( 91 , 92 ). Since Gal-3 association with synthetic glycoclusters and polyvalent cell surface ligands can initiate its self-aggregation ( 38 , 93 ) depending on the length of NT and even leading to bridging of two different counterreceptors, e.g., MUC16(CA125) and EGFR/β 1 -integrin ( 93 95 ), the nature of the ligand(s) appears to modulate this aspect of lectin activity. We first asked the question whether this type of protein design is capable of strong aggregation, when the CRD’s affinity to the ligand is higher than that of the Gal-3/Lac interaction.…”
Section: Resultsmentioning
confidence: 99%
“…S6 ), an activity known from tumor cell growth regulation ( 91 , 92 ). Since Gal-3 association with synthetic glycoclusters and polyvalent cell surface ligands can initiate its self-aggregation ( 38 , 93 ) depending on the length of NT and even leading to bridging of two different counterreceptors, e.g., MUC16(CA125) and EGFR/β 1 -integrin ( 93 95 ), the nature of the ligand(s) appears to modulate this aspect of lectin activity. We first asked the question whether this type of protein design is capable of strong aggregation, when the CRD’s affinity to the ligand is higher than that of the Gal-3/Lac interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, targeting the carboxyl-terminal domain of MUC16, which is retained by the tumor cells after cleavage, can expand the present immunotherapy. In context to this, there are more recent reports of monoclonal antibodies targeting the retained carboxy terminus that have been developed [32, 33, 146, 147]. Another hurdle in the field is the incomplete understanding of the structural and functional diversity of different MUC16 domains along with the aberrant glycoforms and possible splice variants, which are seen during disease condition.…”
Section: Expert Opinionmentioning
confidence: 99%
“…It helped to explain that high MUC16 meant poor prognosis. On the contrary, presence of MUC16 neo-antigen-specific T cells in cancer patients suggested that MUC16 could serve as a potential target for cancer immunotherapy and radioimmunotherapy (16,18,19), which might possibly benefit our subject population.…”
Section: Discussionmentioning
confidence: 99%